Pengendalian Kebakaran Hutan di KPH Sumedang - Bambang Hero Saharjo; Fakhri Sukma Afina (Jurnal Silvikultur Tropika, 2021)
Forest fire is one of the most common forest disturbances. The losses incurred will continue to increase if there is no control efforts are taken. Forest fires in KPH Sumedang in 2014 occur as many as ten times with varied sites including Tomo Utara, Ujung Jaya, Cadas Pangeran, and Tomo, therefore it is necessary to analyze the causes of fire and forest fire control efforts need to be undertaken. This research was conducted by using data triangulation method, and qualitative descriptive analysis. The results showed the cause of the fire due to factors surrounding community activities include forest clearance of land, cigarette butts and land clearing by burning. Forest fire suppression facilities and infrastructure available at KPH Sumedang still do not meet the requirements set forth in LHK Regulation No. 32 of 2016, it is concluded that the efforts already taken to overcome forest fire in KPH Sumedang is not optimal. Keywords: blackout facilities, causes of forest fires, infrastructure, and forest fires